Analisis Kinerja Pegawai Pada Kantor Camat - Muhammad Reza Syahputra; Isnaini Isnaini; Adam Adam (Universitas Medan Area, 2021)
Based on the results of the analysis of the 2020 East Medan District Government Agency Performance Accountability Report, it shows that employee performance is still low, and there are problems that need to be addressed related to apparatus work discipline. The research method used in this research is descriptive with qualitative analysis. Data collection is obtained from interviews, documentation, and observations. The results showed that the work quality of the employees of the East Medan District Head Office, Medan City was still low in terms of handling documents and procedures were still convoluted and slow and not transparent in terms of costs. The work quantity of the employees of the Medan Timur Sub-district Office in Medan City is quite good. The work discipline of the employees of the East Medan Sub-district Office, Medan City, has not yet been implemented as expected by the community. Employees at the Medan Timur Sub-district Office in Medan City have good initiatives in carrying out their duties. As well as the employee's responsibility for all aspects related to the tasks carried out by the employees of the East Medan District Head Office, Medan City is quite good.